Peritoneal Ultrafiltration in the Long-Term Treatment of Chronic Heart Failure Refractory to Pharmacological Therapy - Wojtaszek, Ewa; Grzejszczak, Agnieszka; Niemczyk, Stanislaw; Malyszko, Jolanta; Matuszkiewicz-Rowińska, Joanna (Frontiers in Physiology, 2019)
Abstract Introduction. Despite continuous improvement in the treatment, congestive heart failure (CHF) is a growing health problem and a major cause of mortality and morbidity in the world. There is some positive experience with the removal of the fluid excess via peritoneum in those patients, regardless of their renal function. The aim of this study was to assess the efficacy of peritoneal ultrafiltration (PUF) with a single overnight exchange in the long-term treatment of refractory CHF. Methods. The study included patients with CHF resistant to maximal tolerable pharmacological therapy, who had experienced at least 3 hospitalizations due to CHF during the preceding year and were disqualified from heart transplantation. All of them were treated with single overnight 7.5% icodextrin exchange. Results. There were 15 patients (13 men), aged 72±9 years, with Charlson Comorbidity Index (CCI) 9±1.2, NYHA class IV (11 patients) or III (4 patients), and eGFR 32±11 m/min. They were followed up for 24±8 months (range 12 -43, median 26 months). During the first year, all patients improved their NYHA functional class from 3.7±0.5 to 2.6±0.5; P=0.0005, with stable (34.3±12.4, and 35.6±16.5%, respectively) left ventricular ejection fraction (LVEF), and inferior vena cava (IVC) diameter decreased from 27.8±2.7 to 24.4±3.4 mm; P=0.09. Daily diuresis increased from 867±413 to 1221±680 ml; P=0.25, while the dose of furosemide could be reduced from 620±256 to 360±110 mg/d; P=0.0005, however the kidney function deteriorated, with e-GFR drop from 32±11 to 25.6±13 ml/min/1.73m2; P=0.01). CHF-related hospitalizations decreased from 8.9±2.8 days/month to 1.5±1.2 days/month (P=0.003). Mechanical peritoneal dialysis complications occurred in 5 patients and infectious complications in 4 (peritonitis rate 1 per 72 patient-month). Patient survival was 93% at 1 year and 73% at 2 year. Technique survival was 100%. Conclusions. In patients with refractory CHF, PUF with single icodextrin overnight exchange appears to be a promising therapeutic option as an adjunct to pharmacological management of those who are not transplant candidates. It should be emphasized that the treatment can have a great impact on the quality of life and the total costs of treating these patients.